Recognition of cutting rock hardness by hydraulic cylinder pressure. (October 2021) - He, Ying; Tian, Muqin; Feng, Junling
The online identification of rock hardness is the basis to adjust the rotation velocity and swing velocity of cutting head in real time. To effectively identify the hardness of rock around roadway under different cutting conditions, a novel method based on the hydraulic cylinder pressure signal is proposed. Here, we analyze the changing rule of cutting head load under different rock hardness through dynamic simulation, and the transfer characteristics between cutting dynamic load and the hydraulic cylinder pressure. On this basis, a function model between the hydraulic cylinder pressure and the protodyakonov scale of rock hardness is constructed to identify the rock hardness. The average recognition accuracy of the heavy-duty roadheader in the test is 92.01%. The experimental results indicate that the model can effectively identify the rock hardness under different cutting conditions. This study can be used for online identification of rock hardness and provide reliable basis for the automatic control of roadheader.